Ability of enriched immune T cells to confer resistance in hamsters to infection with Treponema pertenue. - Chan, J K (1979)
This investigation presents the first direct evidence that T cells are involved in resistance to challenge with Treponema pertenue. Enriched T cells from immune hamsters were obtained by sequential filtration through glass and nylon-wool columns. This procedure removed the majority of functional antibody-producing and immunoglobulin-bearing cells. The fractionated cell suspensions were less responsive to stimulation by phytohemagglutinin, lipopolysaccharide, and dextran sulfate, but they were enriched with antithymocyte-sensitive cells and were more responsive to stimulation with concanavalin A. Hamsters receiving fractionated or unfractionated immune cells had no cutaneous lesions 21 days after infection and had significantly lower lymph node weights and fewer treponemes per node than hamsters that received fractionated or unfractionated normal cells. Resistance was transferred with immune cell suspension enriched in T cells despite an absence of anamnestic antibody response to specific treponemal antigens.